Comparative Study of Pension Benefits between Ghana Universities’ Staff Superannuation (GUSSS) and Social Security and National Insurance Trust (SSNIT)Schemes - BOAKYE, KWAME; Addo, Joshua; Awotwe, Eric; Sam, Joyce Anastasia (Ghana Journal of Higher Education Management, 2024)
The practice of using public social security systems as potential welfare and income re-distribution policy tools is widely acknowledged both in academic and practitioner literature. From the perspective of a pension fund member, the most important thing is to receive a retirement benefit that is large enough to improve one’s quality of life in the post-retirement period. This is particularly true when the potential retiree faces the choice of two or more pension schemes; it is therefore useful to undertake a comparative analysis of retirement benefits under different schemes and under different conditions to facilitate an informed choice-making. While there is no consensus on which indicator best measures retirement benefits adequately, the total financial benefits received by the retiree following retirement represents one of the most important indicators of benefits adequacy. To this end, the total financial benefits of retirees under both the GUSSS and SSNIT was assessed. Employing different scenarios including different length of years of working and corresponding monthly contributions as well as the pension rates captured in the focal schemes, it was discovered that GUSSS generates superior retirement benefits side by side SSNIT. Among others, the writers seek to advocate that the board of GUSSS educate members on the superior financial retirement benefits offered by the scheme as compared with SSNIT and to review the pension rights under the GUSSS